Vivências e experiências em educação matemática no município de Parintins/AM - Beltrão, Isabel do Socorro Lobato (2012)
The research is centered in teachers' narratives that supplied and/or they supply Mathematics in the Fundamental and Medium Teaching (1960 - 2010). it Approaches fundamental subjects about practices and educational experiences in the Mathematical Education starting from the teachers' narratives that acted and/or they act in the last five mentioned decades. The Oral History was used as methodology of qualitative research, basing the investigative purposes, preparation, elaboration and analysis of the narratives. It begins with the subject-teachers' outlining, selected, casually, five, being a representative of every decade. It was verified, starting from the narratives, changes happened in the Mathematical Education in the last five decades, because there was qualified teacher's lack, access to books, didactic resources, lack of information, as well as the inherent difficulties to the life in an island in the middle of the Amazonian Forest, in the State of Amazon, North Area of the country. It is expected that has made possible contributions with knowledge, starting from the registrations of the practices and educational experiences and the remeaning of the Mathematical Education in the social relationships and, consequently, in the full exercise of the citizenship.